Gender-Differentiated Impacts of Pension Reform - van Selm, Alexandra (World Bank, Washington, DC, 2012)
Many countries have initiated pension reform to cope with aging populations and fiscally unsustainable pension systems. The reforms often aim to separate the safety net and savings functions of pension systems, and to minimize incentive distortions. They usually involve moving from a single public pillar to a multipillar system, with the latter consisting of a private pillar (with defined contributions) and a more targeted public pillar (with defined benefits). Gender issues arise in pension design because men and women have different employment histories and life expectancies. Women tend to have shorter histories in the formal labor market because they take time off to care for children and are permitted to retire earlier than men. During their working years they also earn less than men, on average (World Bank 2001). As a result, women contribute less to pension systems than men, and are likely to end up with smaller pensions if benefits are closely linked to contributions-as in the defined contribution pillar of new systems. However, the public pillar in new systems often includes a safety net that provides a public transfer to women.